PEMBINAAN AGAMA ISLAM ANAK USIA DINI (Raudhatul Athfal Daruttaqwa Kecamatan Sabangau kota Palangka Raya) - Sukarmi, Sukarmi (LP2M IAIN Palangka Raya, 2014)
Inculcated early education for children unfamiliar with religious activities, one of them through educational institutions such as Raudhatul RA. RA. Daruttaqwa district. Sabangau city of Palangkaraya a religious educational institution for young children to group B via the planting of religious values and development patterns of religious planting a curriculum development in RA. Daruttaqwa district. Sabangau. The study used a qualitative approach with descriptive research approach. The research findings illustrate: First, the material guidance of Islam early childhood group B in RA Daruttaqwa District of Sabangau city of Palangkaraya, guided by the Curriculum 2003 is the standard early childhood education levels of TK / RA, in outline form of education aqidah, moral education / behavior / attitude and education of worship and good deeds. Second, coaching strategies Islam early childhood group B in RA Daruttaqwa District of Sabangau city of Palangkaraya, is the strategy of learning through play, stories and singing are given integrated Islamic education every capability or activity, by combining education aqidah, and ethics / behavior with basic capabilities, the theme and sub themes through activities / techniques / methods in RA Daruttaqwa